Формування якості годівлі повнораціонними комбікормами - Дудін, Володимир Юрійович; Dudin, Volodymyr Yuriyovych; Гаврильченко, Олександр Степанович; Gavrilchenko, Oleksandr Stepanovich; Мудрак, Юрій Ігорович; Mudrak, Yuriy Igorovich; Черниш, Павло Іванович; Chernysh, Pavel Ivanovich (Publishing House «Education and Science», Praha, 2018)
Розроблено структурну схему формування ефективності виробництва продукції тваринництва, з якої встановлено, що найбільш впливовим показником буде «якість годівлі», розглянувши який як певну систему складових було виділено технологічні та технічні ланки, які обумовлені зоотехнічними вимогами. Виділено дві основні складові, які забезпечуються технічною реалізацією процесів – однорідність подрібнення та змішування, при чому останній найбільше залежить від операційної технології приготування та роздавання кормів. The structural scheme of formation of the efficiency of livestock production has been developed, from which it has been established that the most influential indicator will be "quality of feeding", considering that as a certain system of components technological and technical links, which are caused by zootechnical requirements, were allocated. There are two main components that are provided by the technical implementation of the processes - homogeneity of grinding and mixing, whereby the latter depends most on the operating technology of preparation and distribution of feed.
Formation of the quality of feeding full-fodder mixed fodders
Keywords: тваринництво; animal production; ефективність виробництва; production efficiency; якість годівлі; quality of feeding; комбікорм; feed